Grand Tour Correspondence in the Time of War: The Early Stages of the War of the Spanish Succession in the Letters of Henry Bentinck, Viscount Woodstock and His Tutor Paul Rapin-Thoyras (1701–1702) - Green, Michaël (Faces of War, 2024)
Letters sent during a Grand Tour, an early modern educational journey, are often considered important sources for the history of tourism and travel, history of diplomacy or family relations. However, the example of the correspondence of the Anglo-Dutch nobleman Henry Bentinck, Viscount Woodstock and his Huguenot tutor, Paul Rapin-Thoyras with Woodstock’s father, Hans Willem Bentinck, the 1st Earl of Portland, demonstrates that these letters can also contain important information on various military aspects and provide another view on known events such as during the War of the Spanish Succession. In this article, several examples of such cases are examined, together with the alternative, fuller story of the capture of the French Marechal De Villeroy by the Imperial forces. Portland, whose letters are not preserved, was a close friend of King William III of England and was a key figure in Anglo-Dutch politics at the time, thus being in the midst of the events. The analysis is conducted based on Grand Tour letters written in French and sent from various locations both by the pupil and his tutor.